[Leonardo Garcia, Nelson Marcos were elevated to the hall of fame of the SSOT]. - Garcia, Leonardo (Animo Repository, 1998)
Dr. Leonardo Garcia, Marketing Management Chairperson, and Nelson Marcos, Software Technology Dept. faculty, were elevated to the Hall of Fame of the Students' Search for Outstanding Teachers (SSOT), during the awarding ceremonies. The join Roberto Caguingin, Electronics and Communications Engineering faculty.